2003
DOI: 10.1103/physrevlett.90.131101
|View full text |Cite
|
Sign up to set email alerts
|

Solar Flares as Cascades of Reconnecting Magnetic Loops

Abstract: A model for the solar coronal magnetic field is proposed where multiple directed loops evolve in space and time. Loops injected at small scales are anchored by footpoints of opposite polarity moving randomly on a surface. Nearby footpoints of the same polarity aggregate, and loops can reconnect when they collide. This may trigger a cascade of further reconnection, representing a solar flare. Numerical simulations show that a power law distribution of flare energies emerges, associated with a scale-free network… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 24 publications
2
122
0
6
Order By: Relevance
“…Solar flares show scale invariance in their energy release statistics over several orders of magnitude (Aschwanden, 2000;Schwanden and Parnell, 2002) which has been discussed in terms of Self-Organized Criticality (SOC, see e.g. Lu and Hamilton, 1991;Hughes et al, 2003;Dendy et al, 2007). There is also recent evidence, that we review here, in noncascade quantities, such as magnetic energy density, of a signature within the inertial range that shows scaling that correlates with the level of magnetic complexity in the corona Kiyani et al, 2007).…”
Section: S C Chapman Et Al: Solar Wind and Solar Cyclementioning
confidence: 97%
“…Solar flares show scale invariance in their energy release statistics over several orders of magnitude (Aschwanden, 2000;Schwanden and Parnell, 2002) which has been discussed in terms of Self-Organized Criticality (SOC, see e.g. Lu and Hamilton, 1991;Hughes et al, 2003;Dendy et al, 2007). There is also recent evidence, that we review here, in noncascade quantities, such as magnetic energy density, of a signature within the inertial range that shows scaling that correlates with the level of magnetic complexity in the corona Kiyani et al, 2007).…”
Section: S C Chapman Et Al: Solar Wind and Solar Cyclementioning
confidence: 97%
“…One simulation produced a broken powerlaw distribution with a slope of α P = 3.5 for the smallest events, interpreted as nanoflare regime, while a flatter slope of α P = 1.8 was found for the larger flares (Vlahos et al 1995), a difference that is attributed to the anisotropic next-neighbor interactions applied therein. Another study simulated solar flare events as cascades of reconnecting magnetic loops, with the finding of a powerlaw slope of α E = 3.0 for the released energies (Hughes et al 2003). Interacting loops with a length scale L are bisected during a reconnection step into two shorter scales L/2, and the released energies are defined in terms of the length scale therein, i.e., E ∝ L, for which our model predicts indeed an occurrence frequency distribution of N(E) ∝ N(L) ∝ L −S ∝ L −3 (Eq.…”
Section: Observations Of Solar Flaresmentioning
confidence: 99%
“…Subsequently, it has been shown that many networks also have a probability distribution for the number of connections to a node (in network parlance, the degree distribution) that has a power-law tail. Such 'scale-free' networks 25 have been found in an impressively diverse range of fields, including astrophysics, 26 geophysics, 27 information technology, 28 biochemistry, 29,30 ecology 31 and sociology. 32 The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%